Realization of Single Phase Full Bridge Boost Inverter Using Arduino - Farahilla, Wahyu; Faradina, Nevi; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
This paper discusses a single-phase boost inverter that functions to increase and convert DC voltage to AC. A boost inverter is a combination of two DC-DC boost converters that can be operated as an inverter with a load connected in an opposite direction between the two converters. The boost inverter in this final project is implemented with an Arduino UNO328 microcontroller using the sinusoidal pulse width method (SPWM) as a trigger. The output frequency value given varies from 50Hz to 70Hz. In the design of this single-phase boost inverter, it consists of several main components, namely the Arduino microcontroller, which functions as a pulse width modulation signal generator; a MOSFET gate driver using the IR2841S IC functions to switch the IRFP260N MOSFET, where the MOSFET is switched with a constant frequency of 30 kHz and a 5V power supply as a voltage supply for Arduino and a 12V supply voltage for the gate driver; as well as capacitors and inductors. The test results in the design of this single-phase boost inverter run according to the design because the circuit has been able to increase and convert the voltage, namely from an input voltage of 12VDC to 31.59Vac with an output frequency of 50Hz. The selection of component quality in the circuit also affects getting more accurate results